Hermit crabs (Crustacea: Decapoda: Diogenidae) from the KUMEJIMA 2009 Expedition, Japan - Rahayu, Dwi Listyo; Osawa, Masayuki (Zootaxa, 2012)
Hermit crabs fauna of the family Diogenidae in the Kume Island, south Japan, were found to consist of 49 species, ofwhich 47 species were collected during the KUMEJIMA 2009 Expedition. Of the 49 species collected, 20 species, Calci-nus seurati Forest, 1951; Ciliopagurus krempfi (Forest, 1952), Clibanarius corallinus H. Milne Edwards, 1848; Clibanar-ius englaucus Ball & Haig, 1972; Clibanarius rhabdodactylus Forest, 1953; Clibanarius striolatus Dana, 1852; Dardanusbrachyops Forest, 1962; Dardanus robustus Asakura, 2006; Dardanus scutellatus (H. Milne Edwards, 1848); Dardanuswoodmasoni Alcock, 1905; Diogenes holthuisi Asakura & Tachikawa, 2010; Diogenes leptocerus Forest, 1956; Diogenespallescens Whitelegge, 1897; Paguristes macrops Rahayu & Forest, 2009; Paguristes ocellus Komai, 2010; Pseudop-aguristes bicolour Asakura & Kosuge, 2004; Pseudopaguristes bollandi Asakura & McLaughlin, 2003; Pseudopaguristesjanetkae McLaughlin, 2002; Pseudopaguristes laurentae (Morgan & Forest, 1991); and Pseudopaguristes monoporus(Morgan, 1987), are recorded for the first time from Kume Island. Six species, Dardanus brachyops, Diogenes holthuisi, Diogenes leptocerus, Diogenes pallescens, Paguristes macrops, and Pseudopaguristes laurentae, are discussed in detail.